Experimental Robotics IX The 9th International Symposium on Experimental Robotics - Ang, Marcelo H.; Khatib, Oussama; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
The International Symposium on Experimental Robotics (ISER) is a series of bi-annual meetings which are organized in a rotating fashion around North America, Europe and Asia/Oceania. The goal of ISER is to provide a forum for research in robotics that focuses on novelty of theoretical contributions validated by experimental results. The meetings are conceived to bring together, in a small group setting, researchers from around the world who are in the forefront of experimental robotics research. This unique reference presents the latest advances across the various fields of robotics, with ideas that are not only conceived conceptually but also verified experimentally. It collects contributions on the current developments and new directions in the field of experimental robotics, which are based on the papers presented at the Ninth ISER held in Singapore.
Keynote Article -- Human-Centered Robotics -- Identification and Control -- Localization and Map Building -- Medical Robotics -- Manipulation -- Humanoids -- Designs -- Flying Robots -- Multiple Robots -- Walking Robots -- Vision -- Haptics and Augmented Reality -- Perception.
Keywords: Engineering; Artificial intelligence; System theory; Machinery; Control engineering; Robotics; Mechatronics; Automation; Engineering; Robotics and Automation; Control, Robotics, Mechatronics; Artificial Intelligence (incl. Robotics).; Machinery and Machine Elements; Systems Theory, Control; Electronic books